Akibat Hukum Akta Perjanjian Perkawinan yang Tidak Dicatatkan dalam Perkawinan Campuran - Rivanda, Fira Adhisa; Dewi, Gemala (Acta Comitas : Jurnal Hukum Kenotariatan, 2022)
The purpose of this paper is to find out and analyze the arrangement of marriage agreements based on the Marriage Law and the Decision of the Constitutional Court Number 69/PUU-XIII/2015 and to analyze the legal consequences of marriage agreements that are not registered in mixed marriages. This study uses a normative juridical legal research method that is guided by written and unwritten legal norms or norms. The source of this legal research material uses primary legal materials, secondary legal materials. The collection of sources of legal materials is carried out using a literature study technique by examining books, literatures, notes, and reports that are related to the problem being solved. Qualitative analysis is used in this study, the data obtained can be emphasized on quality and analyzed in depth, and the author uses the truth and his own conclusions based on the research. The results of this study indicate that not registering a marriage agreement in mixed marriages does not affect the validity of the marriage agreement itself, it's just that the marriage agreement does not meet the principle of publicity where this can affect third parties.